SPIRITUAL TEACHING DALAM MEMBENTUK KARAKTER SISWA DI SMK ISLAM TSAMRATUL HUDA TAHUNAN JEPARA - Mufid, Fathul (Program Studi Pendidikan Agama Islam, 2016)
SPIRITUAL TEACHING TO FORM STUDENTS’ CHARACTER IN ISLAMIC VOCATIONAL HIGH SCHOOL TSAMRATUL HUDA JEPARA. Spiritual teaching becomes important for education to be seen again as an integral part of Islamic teachings, because in spiritual education, IQ (żaka' aqli), EQ (Zaka’ Zihni), and SQ (Zaka’ Qalbi) are the components which are developed harmoniously. This study was conducted in Tsamratul Huda Islamic vocational high school Tahunan Jepara, which is established under al-Faqih Islamic education foundations. This study aims to describe the implementation of spiritual teaching which has been implemented at the school since 2013 to building students caracter. This study is a qualitative study using triangulation methods in data collection, and using descriptive-analytic method in data analysis. The findings of this study is that there is a change in attitudes, behavior and mindset of the students positively than before the implementation of spiritual teaching. Previously, many students did immoral offense, booze, physical fights, smoking, disrespectful to teachers, absenteeism, and make a chaos in the classroom, so many students drop out of school. After the spiritual teaching models applied in the school, it turns out all forms of the offense had not found anymore.